Mobile, Secure, and Programmable Networking First International Conference, MSPN 2015, Paris, France, June 15-17, 2015, Selected Papers - Boumerdassi, Selma; Bouzefrane, Samia; Renault, Éric (Computer Communication Networks and Telecommunications, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the First International Conference on Mobile, Secure, and Programmable Networking, MSPN 2015, held in Paris, France, in June 2015. The 14 papers presented in this volume were carefully reviewed and selected from 36 submissions. They discuss new trends in networking infrastructures, security, services and applications while focusing on virtualization and cloud computing for networks, network programming, software defined networks (SDN) and their security.